Black mildew - A new disease of mulberry (Morus alba) - TEOTIA*, R.S. (Indian Phytopathology, 2002)
A black incrustation was observed on the foliage of mulberry during the winters of 1991 and 1992 in Berhampore, West Bengal, India. Symptoms were characterised by the presence of a thick, black velvet coating on the upper leaf surfaces. The pathogen was identified as Meliola amphitricha. This constitutes a new disease record on mulberry in India.